Efficacy of Homoeopathy in Gastrointestinal Disorders (Advancements in Homeopathic Research, 2022)
Gastrointestinal infections are the second most common infection affected by human beings. Around 13.46 % of total population suffers from gastrointestinal problems and among them 3.8% has cholelithiasis. Homoeopathy is a complementary, conventional and alternative therapy useful in gastrointestinal disorders. Homoeopathic treatment is proved more cost effective system compared to other system of medicines. A retrospective analysis had been conducted among patients those who had visited the gastroenterology unit out patient department of NHRIMH, Kottayam, Kerala during January 2021 and February 2021 (2 months) to assess the most frequent gasterointestinal disorders their common indicated medicines. Conclusion: The above study reveals that there is clear cut evidence that the homoeopathic medicine is having significant action over gasterointestinal disorders which cures this patient without any side effects when administered based on principles of homoeopathy.
Keywords: Gastrointestinal infections; population; cholelithiasis; Homoeopathy; complementary; conventional